The investigation of optimum condition of natural rubber epoxidation reaction in latex phase - Norma Arisanti Kinasih; Hani Handayani; Mohammad Irfan Fathurrohman; Asron Ferdian Falaah (Majalah Kulit, Karet, dan Plastik, 2021)
Natural rubber (NR) latex epoxidation is a chemical modifcation of natural rubber to produce natural rubber with higher polarity (oil resistant) which is commonly called epoxidized natural rubber (ENR). ENR is produced from the reaction of natural rubber latex with performic acid. Performic acid is formed from in situ reaction between formic acid and hydrogen peroxide. During epoxidation process, the carboxyl group of natural rubber is converted into epoxy group and various side reaction products such as carbonyl, hydroxyl, and hydro furan. These side products must be minimalized to optimize the epoxy level. The epoxidation reaction was carried out at 70 °C for 6 hours using 2 types of latex: fresh latex (FL) and concentrated latex (CL). The addition of reactant was varied in two ways: dropwise (coded “1”) and poured all at once (coded “2”). The epoxy product and rate constant (k) were analyzed to obtain optimum reaction condition. The epoxy and side reaction content were determined by Attenuated Resonance Fourier Transform Infrared (ATR-FTIR). The slope of epoxy-time plotting curve was determined as ENR rate constant (k). The optimum NR epoxidation reaction was achieved in CL2, which exhibited lowest value of side reaction and highest value of k (2.8082x10-5 L mol-1 sec-1).